10 - year experience in the application of biological therapy to patients with juvenile idiopathic arthritis - Zaure Mukusheva; Maikesh Asylbekova; Zhanara Albekova; Leyla Sadibekova (National Scientific Medical Center, 2017)
The article presents the experience of using biological agents for the treatment of children with juvenile idiopathic arthritis in the department of rheumatology of the Corporate Fund "University Medical Center" of the National Research Center for Maternal and Child Health.